2019
DOI: 10.1177/000313481908500951
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Recovery after Surgery (ERAS) Protocols Expanded over Multiple Service Lines Improves Patient Care and Hospital Cost

Abstract: Enhanced recovery after surgery (ERAS) may improve patients’ postoperative course. Our center implemented the ERAS protocol for the colorectal service in 2016, and then expanded to multiple service lines over the course of 1.5 years. Our aim was to determine whether broad implementation of ERAS protocols across different service lines could improve patient care. All ERAS patients from 2018 were captured prospectively. For each service line using ERAS, one full year of data preceding ERAS was compared. ERAS ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 19 publications
(23 reference statements)
2
15
0
1
Order By: Relevance
“…Concept and institutional implementation of evidence-based Enhanced Recovery After Surgery (ERAS) clinical pathways aim to incorporate best practice and improve measurable clinical outcomes, including pain, mortality, hospital length of stay, patient satisfaction, and costs. [6][7][8][9] ERAS pathways have been published to guide the management of patients undergoing different surgery types, including colorectal, 10 gynecologic, 11 and thoracic surgeries. 12 Also, outside of published institutional protocols, 9,[13][14][15][16][17][18][19][20][21][22][23][24] the ERAS Society recently published evidence-based ERAS pathway recommendations for lumbar fusion.…”
mentioning
confidence: 99%
“…Concept and institutional implementation of evidence-based Enhanced Recovery After Surgery (ERAS) clinical pathways aim to incorporate best practice and improve measurable clinical outcomes, including pain, mortality, hospital length of stay, patient satisfaction, and costs. [6][7][8][9] ERAS pathways have been published to guide the management of patients undergoing different surgery types, including colorectal, 10 gynecologic, 11 and thoracic surgeries. 12 Also, outside of published institutional protocols, 9,[13][14][15][16][17][18][19][20][21][22][23][24] the ERAS Society recently published evidence-based ERAS pathway recommendations for lumbar fusion.…”
mentioning
confidence: 99%
“…To address these concerns, most modern studies of ERAS implementation assess for readmission rate and many also look at complication rate following surgery. A total of 21 of the published ERAS intervention studies to date have reported on complications, with rates of complications prior to ERAS introduction ranging from 5% to 70%, depending on the population/surgery studied and the grade of complication reported [ 11 , 14 , 24 ]. The PROFAST study looked at specific complications between the ERAS and conventional management arms of the study and found no statistically significant difference in major (Grade IIIB-V) complications between the 2 arms, but noted a 10% reduction in postoperative ileus with ERAS interventions.…”
Section: Outcomes Of Eras Implementationmentioning
confidence: 99%
“…The principles of enhanced recovery, when fully implemented, have been demonstrated to reduce the length of hospital stay (LOS), morbidity, and convalescence, without an increase in readmission rates or complications [ 4 , 18 , 19 , 20 ]. Enhanced recovery pathways (ERP) can be considered a Quality Improvement (QI) intervention and are an inter-professional and multimodal approach to care [ 21 , 22 , 23 , 24 , 25 , 26 ]. ERP seeks to optimize patient care before, during, and after surgery to minimize the surgical stress response.…”
Section: Problem Descriptionmentioning
confidence: 99%